Using brochure as a media in teaching reading descriptive text among the eight grade students of SMPN 1 Jiwan - Laelly Kartikasari; Nuri Ati Ningsih; Fitra Pinandhita (Universitas PGRI Madiun, 2018)
The objectives of this research are: 1) to know how is the implementation of Brochure to teach reading for the eight grade students of SMPN 1 Jiwan, 2) to find out the advantages of the implementation of brochure to teach reading for the eight grade students of SMPN 1 Jiwan, 3) to find out the disadvantages of teaching reading descriptive text to the eight grade students of SMP N 1 Jiwan in schoooling year of 2016/2017. The research approach and type of this research is descriptive qualitative research. This research was held on SMP N 1 Jiwan, focus on the eight grade students. The source of data of this research are social situation, participant and document. The participant of this research are the students of class VIII G. In this research, the researcher as observer in the class. To get the data, the researcher uses observation, interview, and documentation. The technique of data analysis that used in this research are data condensation, data display, and drawing or verifying conclusion. The result of the research are 1) the implementation of Brochure as a media to teach reading divided into three stages, they are (a) pre- activities included greeting, checking students’ attendance, and build background knowledge, (b) whilst activities included giving the explanation about the materials, and the implementation of brochure as a media, (c) post activities included review the materials, asking the students difficulties, gives a conclusion, and closing. 2) the advantages and disadvantages of the implementation of brochure as a media. The advantages are to increase the students interesting in following teaching reading, this media can helps the students to finish their task to answer all the questions, and to makes the students do not feel bored in teaching reading process. While, the disadvantages by using brochure that are some students still passive during teaching reading process, the students have less vocabularies make the students feel difficult to translate the meaning of the text. Based on the research, the researcher gives some suggestion. The teacher is suggested to use this media especially in teaching reading descriptive text. The students should increase their vocabulary in order to makes the students be easier to understand the meaning of the text. The future researcher are suggest to conduct other research in english teaching especially for teaching reading.